High-transmittance photovoltaic O-shaped glass and preparation method thereof
By optimizing the glass raw material formula and preparation process, the ultraviolet and visible light transmittance of high-transmittance photovoltaic O-type glass has been improved, and its mechanical strength and thermal stability have been enhanced. This solves the problems of low ultraviolet light utilization efficiency and high production cost in existing technologies, and is suitable for building-integrated photovoltaics and centralized photovoltaic power plants.
Patent Information
- Application Number
- CN202511798442.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-02
- Publication Date
- 2026-01-23
AI Technical Summary
Existing high-transmittance photovoltaic O-type glass has low ultraviolet light utilization efficiency, makes it difficult to achieve full-spectrum transmittance, and has high production costs, insufficient mechanical properties, and inadequate environmental adaptability.
Glass raw materials with a specific formula (quartz sand, alumina, sodium carbonate, calcium carbonate, magnesium oxide, cerium oxide, titanium oxide, zirconium oxide, sodium sulfate, and iron oxide) are used and processed through air pressure-assisted centrifugal forming, annealing, and nanoscale anti-reflective coating, combined with secondary heat treatment to optimize electronic energy levels and glass network structure.
It significantly improves the transmittance of ultraviolet and visible light, enhances mechanical strength and thermal stability, improves the photoelectric conversion efficiency of photovoltaic cells, and reduces production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of O-type glass, in particular to a high-transmittance photovoltaic O-type glass and a preparation method thereof. BACKGROUND
[0002] As a key component of photovoltaic modules, high-transmittance photovoltaic O-type glass is mainly used to maximize light transmittance to improve the photoelectric conversion efficiency of solar cells, while also considering mechanical strength and environmental durability. In recent years, with the rapid development of the photovoltaic industry, high-transmittance glass technology has made significant progress. Traditional methods achieve high light transmittance by optimizing glass matrix composition (such as low-iron glass), surface anti-reflection coating (such as SiO2 or TiO2 single / multilayer coating), and surface texturing (such as micron-scale etching or embossing). In the visible light band (400-700 nm), the light transmittance is usually above 90%. In addition, some studies have explored functional additives or composite materials to improve the glass's anti-ultraviolet aging performance or thermal stability. For example, by doping metal oxides (such as Al2O3 or ZrO2) to enhance the chemical stability of the glass, or using plasma-enhanced chemical vapor deposition (PECVD) technology to deposit nano-scale anti-reflection coatings to reduce surface reflection loss. These technological advancements have significantly promoted the application of photovoltaic glass in high-performance modules, particularly in the fields of building-integrated photovoltaics (BIPV) and centralized photovoltaic power stations. However, existing technologies still have limitations in spectral utilization efficiency, material cost and performance balance, and complex environmental adaptability, limiting the overall performance improvement of photovoltaic modules.
[0003] Although existing high-transmittance photovoltaic O-type glass performs well in visible light transmission, its utilization efficiency of ultraviolet light (300-400 nm) in the solar spectrum is generally low. Ultraviolet light is usually absorbed or reflected by the glass matrix, which cannot be effectively transmitted to the photovoltaic cell, resulting in insufficient spectral utilization. Traditional glass matrix optimization focuses on physical structure adjustment (such as refractive index optimization or surface scattering design), while there is little research on chemical doping of electronic energy levels, especially the lack of exploration of mechanisms for converting ultraviolet light to visible light. In addition, existing anti-reflection coatings and texturing technologies have limitations in wide-band spectral response, making it difficult to achieve high transmittance across the entire spectrum, especially in the ultraviolet light band. On the other hand, glass formulations doped with metal oxides can improve mechanical properties or weather resistance, but often introduce additional light absorption or scattering, reducing light transmittance, and the doping process is complex, increasing production costs. These shortcomings make it difficult for existing photovoltaic O-type glass to fully utilize the energy of the entire solar spectrum, limiting the overall photoelectric conversion efficiency of photovoltaic cells. SUMMARY
[0004] The present application provides a high-transmittance photovoltaic O-type glass, which comprises the following raw materials by weight percentage: Quartz sand 65-70%; Alumina 8-12%; Sodium carbonate 12-15%; Calcium carbonate 5-8%; Magnesium oxide 2-4%; Cerium oxide 0.5-1.0%; Titanium oxide 0.1-0.5%; Zirconium oxide 0.1-0.3%; Sodium sulfate 0.5-1.0%; Iron oxide 0.01-0.05%.
[0005] As a preferred technical solution of the photovoltaic O-type glass, the purity of the quartz sand is not less than 99.8%, the silicon dioxide content is ≥99.5%, and the particle size is controlled at 0.1-0.4 mm.
[0006] As a preferred technical solution of the photovoltaic O-type glass, the weight ratio of cerium oxide and titanium oxide is 2.5:1 to 3.5:1.
[0007] As a preferred technical solution of the photovoltaic O-type glass, the iron oxide content is controlled at 0.01-0.03%.
[0008] A method for preparing a photovoltaic O-type glass, comprising the following steps: a) According to the weight percentage ratio of claim 1, the quartz sand, alumina, sodium carbonate, calcium carbonate, magnesium oxide, cerium oxide, titanium oxide, zirconium oxide, sodium sulfate and iron oxide are mixed uniformly to obtain a mixed raw material; b) The mixed raw material is placed in a melting furnace and melted at 1420-1480℃ for 2.5-3.5 hours to form a uniform glass melt; c) The glass melt is formed by a gas pressure assisted centrifugal forming process, the mold rotation speed is controlled at 500-2000 rpm, the solidification temperature is room temperature to 80℃, the forming speed is 10-20 m / min, and the gas pressure is controlled at 0.1-0.2 MPa to obtain a glass substrate; d) The glass substrate is annealed at an annealing temperature of 560-600℃ for 1.5-2 hours to eliminate internal stress; e) The annealed glass substrate is polished and a nano-scale anti-reflection coating is applied, and the coating thickness is 100-120 nm.
[0009] As a preferred technical solution of the method for preparing a photovoltaic O-type glass, the melting process in step b) is carried out under nitrogen or argon protection, and the gas pressure is controlled at 0.1-0.2 MPa.
[0010] As a preferred technical solution of the method for preparing the photovoltaic O-type glass, the anti-reflection coating in step e) is a composite material of silicon dioxide and titanium dioxide, and the refractive index of the coating is controlled to be between 1.22 and 1.28.
[0011] As a preferred technical solution of the method for preparing the photovoltaic O-type glass, the thickness of the glass substrate in the float process in step c) is controlled to be between 2.0 and 3.2 mm, and the surface flatness deviation is less than or equal to 0.05 mm / m.
[0012] As a preferred technical solution of the method for preparing the photovoltaic O-type glass, a secondary heat treatment is further included after step e), the temperature is between 420 and 450 DEG C, and the holding time is between 0.5 and 0.8 hours.
[0013] The high-transmittance photovoltaic O-type glass of the present application exhibits significant beneficial effects through optimization of the formula and the preparation process. The experimental data of Examples 1 to 5 show that the ultraviolet light transmittance of the glass is between 89.5% and 90.3%, the visible light transmittance is between 93.0% and 93.7%, the bending strength is between 118 and 122 MPa, and the transmittance change rate after thermal cycling is only between 0.3% and 0.6%. Through synergistic doping of cerium oxide (0.6% to 0.9%) and titanium oxide (0.2% to 0.35%) at a weight ratio of 2.5:1 to 3.5:1, combined with nitrogen or argon protection melting (gas pressure 0.1 to 0.2 MPa), 105 to 115 nm anti-reflection coating (refractive index 1.22 to 1.28), and 420 to 450 DEG C secondary heat treatment, the full-spectrum utilization efficiency, mechanical strength, and thermal stability are significantly improved. In contrast, the performance of Comparative Examples 1 to 4 is significantly decreased (ultraviolet light transmittance 85.8% to 87.2%, visible light transmittance 92.0% to 92.3%, bending strength 110 to 115 MPa, and thermal stability 0.8% to 1.1%) due to the removal of cerium oxide and titanium oxide, the absence of inert gas protection, or insufficient coating thickness. These advantages are due to electronic energy level regulation, defect suppression, and optical optimization, which enable the glass of the present application to effectively improve the photovoltaic cell photoelectric conversion efficiency, while taking into account durability and cost-effectiveness, and are suitable for building integrated photovoltaics and centralized photovoltaic power stations, and have significant environmental and economic value. DETAILED DESCRIPTION
[0014] In order to make the above-mentioned objects, features and advantages of the present application more apparent and easy to understand, the specific embodiments of the present application will be described in detail below in conjunction with the description of the examples.
[0015] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the scope of the present application, therefore the present application is not limited to the specific examples disclosed below.
[0016] Second, the term "one embodiment" or "an embodiment" as may appear in various places in the specification are not necessarily all referring to the same embodiment, nor are they necessarily mutually exclusive or alternative implementations.
[0017] Embodiments Embodiment 1 Raw material ratio (weight percentage): Quartz sand: 67% (purity > 99.8%, silica content > 99.5%, particle size 0.1-0.4 mm) Alumina: 10% Sodium carbonate: 13% Calcium carbonate: 6% Magnesium oxide: 3% Cerium oxide: 0.7% Titanium oxide: 0.2% Zirconium oxide: 0.2% Sodium sulfate: 0.8% Iron oxide: 0.02% Preparation process: 1. Raw material mixing: According to the above ratio, the quartz sand, alumina, sodium carbonate, calcium carbonate, magnesium oxide, cerium oxide, titanium oxide, zirconium oxide, sodium sulfate and iron oxide are placed in a high-speed mixer and stirred at 500 rpm for 30 minutes to ensure uniform mixing, obtaining the mixed raw materials.
[0018] 2. Melting: The mixed raw materials are placed in a high-temperature melting furnace and melted at 1450°C for 3 hours, with nitrogen gas (gas pressure 0.15 MPa) protection during the melting process to prevent oxidation and bubble formation, and the stirring speed is 50 rpm, forming a uniform glass melt.
[0019] 3. Forming: The glass melt is formed by air pressure assisted centrifugal forming process, the mold rotation speed is controlled at 500 rpm, the solidification temperature is room temperature to 80°C, the forming speed is 10 m / min, and the air pressure is controlled at 0.1 MPa, obtaining a glass substrate with a thickness of 2.5 mm.
[0020] 4. Annealing: The formed glass substrate is placed in an annealing furnace and annealed at 580°C for 1.8 hours, with a cooling rate of 2°C / min to eliminate internal stress.
[0021] 5. Surface treatment: After annealing, the glass substrate is polished on both sides with a surface flatness deviation of <0.05 mm / m, and then a 110 nm thick composite antireflection coating of silicon dioxide and titanium dioxide (refractive index 1.25) is applied by magnetron sputtering, wherein the mass ratio of SiO2 to TiO2 nanoparticles is 7:3.
[0022] 6. Secondary heat treatment: The coated glass substrate is placed in a heat treatment furnace for 0.6 hours at 430°C, cooled to room temperature, and the bonding strength of the coating to the substrate is enhanced.
[0023] 7. Inspection and packaging: The glass substrate is subjected to quality inspection (including light transmittance, flatness and thickness), and after passing the inspection, it is manually packaged and stored.
[0024] Example 2 Raw material ratio (weight percentage): Quartz sand: 68% Alumina: 9% Sodium carbonate: 14% Calcium carbonate: 5.5% Magnesium oxide: 2.5% Cerium oxide: 0.8% Titanium oxide: 0.3% Zirconium oxide: 0.15% Sodium sulfate: 0.6% Iron oxide: 0.03% Preparation process: 1. Raw material mixing: The raw materials are placed in a mixer according to the ratio, stirred at 600 rpm for 25 minutes, and mixed uniformly.
[0025] 2. Melting: Melting at 1430°C for 2.8 hours, with argon gas (gas pressure 0.1 MPa) and stirring speed 60 rpm, forming a uniform melt.
[0026] 3. Forming: By air pressure assisted centrifugal forming process, the mold rotation speed is controlled at 2000 rpm, the solidification temperature is room temperature to 80°C, the forming speed is 20 m / min, and the air pressure is controlled at 0.2 MPa, to obtain a glass substrate with a thickness of 2.3 mm.
[0027] 4. Annealing: Annealing at 570°C for 1.6 hours, cooling rate 2.5°C / min.
[0028] 5. Surface treatment: After polishing on both sides, a 105 nm antireflection coating (refractive index 1.22) is applied, wherein the mass ratio of SiO2 to TiO2 nanoparticles is 7:3.
[0029] 6. Secondary heat treatment: 420°C for 0.5 hours, cooled to room temperature.
[0030] 7. Inspection and packaging: after inspection, package and store.
[0031] Example 3 Raw material ratio: Quartz sand: 66% Alumina: 11% Sodium carbonate: 12.5% Calcium carbonate: 7% Magnesia: 3.5% Ceria: 0.6% Titanium oxide: 0.25% Zirconia: 0.25% Sodium sulfate: 0.7% Iron oxide: 0.015% Preparation process: 1. Raw material mixing: mix uniformly for 28 minutes at 550 rpm.
[0032] 2. Melting: melt at 1460℃ for 3.2 hours under nitrogen protection (0.2 MPa of air pressure), stirring speed 55 rpm.
[0033] 3. Forming: through air pressure assisted centrifugal forming process, control the mold rotation speed at 1000 rpm, solidification temperature at room temperature to 80℃, forming speed at 15 m / min, air pressure control at 0.2 MPa, thickness 2.8 mm.
[0034] 4. Annealing: anneal at 590℃ for 1.9 hours, cooling rate 2℃ / min.
[0035] 5. Surface treatment: after polishing, apply 115 nm anti-reflective coating (refractive index 1.28), in which the mass ratio of SiO2 and TiO2 nanoparticles is 7:3.
[0036] 6. Secondary heat treatment: 440℃ for 0.7 hours.
[0037] 7. Inspection and packaging: after inspection, package and store.
[0038] Example 4 Raw material ratio: Quartz sand: 69% Alumina: 8.5% Sodium carbonate: 13.5% Calcium carbonate: 6.5% Magnesia: 2.8% Ceria: 0.9% Titanium oxide: 0.35% Zirconia: 0.18% Sodium sulfate: 0.9% Iron oxide: 0.025% Preparation process: 1. Mixing ingredients: Stir at 520 rpm for 30 minutes until well mixed.
[0039] 2. Melting: Melt at 1440℃ for 2.7 hours under argon protection (pressure 0.15 MPa) and stirring speed 50 rpm.
[0040] 3. Molding: Float process, molding temperature 1070℃, tin bath temperature 970℃, speed 12.5 m / min, thickness 2.4mm.
[0041] 4. Annealing: Anneal at 575℃ for 1.7 hours, with a cooling rate of 2.2℃ / min.
[0042] 5. Surface treatment: After polishing, a 108 nm antireflective coating (refractive index 1.24) is applied, wherein the mass ratio of SiO2 to TiO2 nanoparticles is 7:3.
[0043] 6. Secondary heat treatment: Hold at 435℃ for 0.65 hours.
[0044] 7. Inspection and Packaging: After passing inspection, the product is packaged and put into storage.
[0045] Example 5 Raw material ratio: Quartz sand: 65.5% Alumina: 11.5% Sodium carbonate: 14.5% Calcium carbonate: 5.8% Magnesium oxide: 3.2% Cerium oxide: 0.75% Titanium oxide: 0.28% Zirconia: 0.22% Sodium sulfate: 0.75% Iron oxide: 0.018% Preparation process: 1. Mixing ingredients: Stir at 580 rpm for 27 minutes until well mixed.
[0046] 2. Melting: Melt at 1470℃ for 3.3 hours under nitrogen protection (pressure 0.18 MPa) and stirring speed 52 rpm.
[0047] 3. Molding: Pneumatic-assisted centrifugal molding process, controlling the mold rotation speed at 1500 rpm, curing temperature from room temperature to 80℃, molding speed at 20 m / min, air pressure controlled at 0.2 MPa, and thickness at 2.6 mm.
[0048] 4. Annealing: 585°C for 1.85 hours, cooling rate 2.3°C / min.
[0049] 5. Surface treatment: 112 nm anti-reflective coating (refractive index 1.26) applied after polishing, with a mass ratio of SiO2to TiO2nanoparticles of 7:3.
[0050] 6. Secondary heat treatment: 450°C for 0.8 hours.
[0051] 7. Inspection and packaging: packaged after inspection.
[0052] Comparative Example Comparative Example 1 : Removal of cerium oxide raw material ratio: Quartz sand: 67.7% (increased to make up for the absence of cerium oxide) Alumina: 10% Sodium carbonate: 13% Calcium carbonate: 6% Magnesium oxide: 3% Cerium oxide: 0% (difference from Example 1) Titanium oxide: 0.2% Zirconium oxide: 0.2% Sodium sulfate: 0.8% Iron oxide: 0.02% Preparation process: exactly the same as Example 1, only the raw material ratio removes cerium oxide.
[0053] Comparative Example 2: Removal of titanium oxide raw material ratio: Quartz sand: 67.2% (increased to make up for the absence of titanium oxide) Alumina: 10% Sodium carbonate: 13% Calcium carbonate: 6% Magnesium oxide: 3% Cerium oxide: 0.7% Titanium oxide: 0% (difference from Example 1) Zirconium oxide: 0.2% Sodium sulfate: 0.8% Iron oxide: 0.02% Preparation process: exactly the same as Example 1, only the raw material ratio removes titanium oxide.
[0054] Comparative Example 3: No inert gas protection Raw material ratio: exactly the same as Example 1. Preparation process: Raw material mixing: same as Example 1.
[0055] Melting: melted at 1450°C for 3 hours without nitrogen protection (difference from Example 1), stirring speed 50 rpm.
[0056] Shaping: Same as Example 1.
[0057] Annealing: Same as Example 1.
[0058] Surface treatment: Same as Example 1.
[0059] Secondary heat treatment: Same as Example 1.
[0060] Inspection and packaging: Same as Example 1.
[0061] Comparative Example 4: Insufficient anti-reflective coating thicknessRaw material mixing: Same as Example 1.
[0062] Melting: Same as Example 1.
[0063] Shaping: Same as Example 1.
[0064] Annealing: Same as Example 1.
[0065] Surface treatment: After polishing on both sides, an anti-reflective coating with a thickness of 90 nm (refractive index 1.5) was applied, which is different from the 110 nm in Example 1.
[0066] Secondary heat treatment: Same as Example 1.
[0067] Inspection and packaging: Same as Example 1 Performance test methods 1. Transmittance test Instrument: UV-Vis spectrophotometer Method: Place the glass sample in the spectrophotometer and measure the transmittance in the 300-400 nm (ultraviolet light) and 400-700 nm (visible light) wavelength ranges, recording the average value.
[0068] 2. Mechanical strength test Instrument: Universal testing machine Method: Use the three-point bending method, with a span of 50 mm and a loading speed of 0.5 mm / min, to measure the bending strength of the glass (unit: MPa).
[0069] 3. Thermal stability test Instrument: Thermal cycle test chamber Method: Perform 100 thermal cycles between -40°C and 85°C on the glass sample, with each cycle lasting 30 minutes, and measure the change rate of transmittance before and after the cycle (unit: %).
[0070] Table 1 lists the formulations and process parameters
[0071] Table 2 is the experimental data of Examples 1-5 and Comparative Examples 1-4
[0072] In combination with Examples 1-5 and Table 2, it can be seen that the performance range of the high-transmittance photovoltaic O-glass is as follows: the ultraviolet light transmittance of Examples 1-5 is 89.5%-90.3%, the visible light transmittance is 93.0%-93.7%, the bending strength is 118-122 MPa, and the transmittance change rate after thermal cycling is 0.3%-0.6%, which indicates that the formulation and process in the patent application significantly improve the light transmittance performance, mechanical strength, and thermal stability of the glass.
[0073] In combination with Examples 1, Comparative Example 1, and Comparative Example 2 and Table 2, it can be seen that the ultraviolet light transmittance of Example 1 reaches 89.5%, the visible light transmittance is 93.2%, the bending strength is 120 MPa, and the transmittance change rate after thermal cycling is only 0.5%. In contrast, the ultraviolet light transmittance of Comparative Example 1 (removing cerium oxide) decreases to 85.8%, the visible light transmittance is 92.0%, the bending strength is 110 MPa, and the transmittance change rate after thermal cycling increases to 1.1%; the ultraviolet light transmittance of Comparative Example 2 (removing titanium oxide) is 86.5%, the visible light transmittance is 92.3%, the bending strength is 112 MPa, and the transmittance change rate after thermal cycling is 1.0%. The experimental results show that the synergistic doping of cerium oxide and titanium oxide at a weight ratio of 3.5:1 significantly improves the spectral performance, mechanical strength, and thermal stability of the glass. Cerium oxide reduces the ultraviolet light absorption edge through 4f-5d electron transition, optimizing the spectral utilization efficiency; titanium oxide enhances light scattering regulation and the stability of the Si-O-Si network structure, reducing defect formation. The synergistic effect of the two optimizes the electronic energy level distribution and the glass network structure, ensuring high light transmittance and excellent mechanical and thermal stability. In contrast, Comparative Example 1 has a blue shift in the ultraviolet absorption edge due to the absence of cerium oxide, resulting in a significant decrease in transmittance; Comparative Example 2 lacks titanium oxide, weakening light scattering regulation and network stability, and the overall performance deteriorates.
[0074] As can be seen from Example 1, Comparative Example 3 and Table 2, the ultraviolet light transmittance of Example 1 is 89.5%, the visible light transmittance is 93.2%, the bending strength is 120 MPa, and the transmittance change rate after thermal cycling is 0.5%. In contrast, the ultraviolet light transmittance of Comparative Example 3 (without inert gas protection) is reduced to 86.7%, the visible light transmittance is 92.1%, the bending strength is 112 MPa, and the thermal stability is 1.1%, which is reduced by 2.8%, 1.1%, 6.7% and 0.6%, respectively. This shows that inert gas protection is crucial to the performance of the glass. Mechanistically, the nitrogen protection (0.15 MPa) during the 1450°C melting process of Example 1 effectively suppresses the oxidation reaction and bubble generation, reduces the micro defects in the glass melt, ensures a uniform Si-O-Si network structure and high transmittance; at the same time, the reduced defects improve the mechanical strength and thermal stability of the glass. Due to the lack of nitrogen protection, the bubble and oxide impurities in the melt of Comparative Example 3 increase, leading to increased light scattering, reduced transmittance, and increased network structure defects, which deteriorate the mechanical strength and thermal stability.
[0075] As can be seen from Example 1, Comparative Example 4 and Table 2, the ultraviolet light transmittance of Example 1 is 89.5%, the visible light transmittance is 93.2%, the bending strength is 120 MPa, and the transmittance change rate after thermal cycling is 0.5%. In contrast, the ultraviolet light transmittance of Comparative Example 4 (antireflection coating thickness of 90 nm) is reduced to 87.2%, the visible light transmittance is 92.3%, the bending strength is 115 MPa, and the thermal stability is 0.8%, which is reduced by 2.3%, 0.9%, 4.2% and 0.3%, respectively. This shows that the thickness of the antireflection coating is crucial to the transmittance performance. Mechanistically, the 110 nm thick silica and titanium dioxide composite antireflection coating (refractive index 1.25) of Example 1 effectively reduces the surface reflection loss in the 300-700 nm band by optimizing the optical path difference and refractive index matching, and improves the full-spectrum transmittance; a suitable coating thickness also enhances the adhesion between the coating and the substrate, improving the thermal stability. Due to the insufficient coating thickness (90 nm) of Comparative Example 4, the light interference effect is weakened, the reflection loss is increased, leading to a decrease in transmittance; at the same time, the thinner coating is prone to micro-cracks during thermal cycling, reducing the thermal stability. This optimized design of coating thickness significantly improves the spectral performance and durability.
[0076] The preferred embodiments of the application have been described above with reference to the drawings, but the application is not limited to these embodiments, and those skilled in the art can modify the technical solutions described in the foregoing embodiments, or make equivalent replacements to some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the application shall be included in the protection scope of the application.
Claims
1. A high-transmittance photovoltaic O-type glass, characterized in that, The raw materials include the following weight percentages: Quartz sand 65-70%; Alumina 8-12%; Sodium carbonate 12-15%; Calcium carbonate 5-8%; Magnesium oxide 2-4%; Cerium oxide 0.5-1.0%; Titanium oxide 0.1-0.5%; Zirconia 0.1-0.3%; Sodium sulfate 0.5-1.0%; Iron oxide 0.01-0.05%.
2. The photovoltaic O-type glass according to claim 1, characterized in that, The quartz sand has a purity of not less than 99.8%, a silica content of ≥99.5%, and a particle size controlled between 0.1 and 0.4 mm.
3. The photovoltaic O-type glass according to claim 1, characterized in that, The weight ratio of cerium oxide to titanium oxide is 2.5:1 to 3.5:
1.
4. The photovoltaic O-type glass according to claim 1, characterized in that, The iron oxide content is controlled between 0.01% and 0.03%.
5. A method for preparing the photovoltaic O-type glass according to any one of claims 1-4, characterized in that, Includes the following steps: a) According to the weight percentage ratio described in claim 1, quartz sand, alumina, sodium carbonate, calcium carbonate, magnesium oxide, cerium oxide, titanium oxide, zirconium oxide, sodium sulfate and iron oxide are mixed evenly to obtain a mixed raw material; b) Place the mixed raw materials in a melting furnace and melt them at 1420-1480℃ for 2.5-3.5 hours to form a homogeneous glass melt; c) The glass melt is formed by a pneumatic-assisted centrifugal molding process, with the mold rotation speed controlled at 500-2000 rpm, the curing temperature at room temperature to 80℃, the molding speed at 10-20 m / min, and the air pressure controlled at 0.1-0.2 MPa, to obtain a glass substrate; d) Anneal the glass substrate at a temperature of 560-600℃ for 1.5-2 hours to eliminate internal stress. e) Polish the surface of the annealed glass substrate and apply a nanoscale antireflective coating with a thickness of 100-120 nm.
6. The preparation method according to claim 6, characterized in that, In step b), the melting process is carried out under nitrogen or argon protection, with the gas pressure controlled at 0.1-0.2 MPa.
7. The preparation method according to claim 6, characterized in that, The antireflective coating in step e) is a composite material of silicon dioxide and titanium dioxide, and the refractive index of the coating is controlled between 1.22 and 1.
28.
8. The preparation method according to claim 6, characterized in that, In step c), the thickness of the glass substrate in the float glass process is controlled between 2.0 and 3.2 mm, and the surface flatness deviation is ≤0.05 mm / m.
9. The preparation method according to claim 6, characterized in that, Step e) is followed by a secondary heat treatment at a temperature of 420-450°C for a holding time of 0.5-0.8 hours.